The Effect of Ethanol Extract of Jicama (Pachyrhizus erosus) on Apoptosis Index and Endometrial Thickness in White Rats (Rattus norvegicus) Ovariectomy Model - Meirna Eka Fitriasnani; Mayasari Putri Ardela; Clara Anabel Galla; Ayu Tiska Arlik Insiati (STRADA : Jurnal Ilmiah Kesehatan, 2025)
Menopause is the permanent cessation of menstruation due to the loss of ovarian follicular activity, which marks the end of a woman's reproductive function. During menopause, estrogen levels decrease, triggering oxidative stress, leading to cell death (apoptosis) and a decrease in endometrial thickness, which can lead to symptoms such as hot flushes, sleep disturbances, decreased sexual desire, and changes in the menstrual cycle. Menopause-related symptoms are considered natural and are often ignored because they are related to a woman's menstrual cycle. Menopause-related problems increase morbidity and mortality due to inadequate treatment, so interventions are needed to reduce morbidity by alleviating symptoms during menopause.